Prospective, Randomized Comparison of Cervical Total Disk Replacement Versus Anterior Cervical Fusion: Results at 48 Months Follow-up. Issue 4 (May 2015) - Hisey, Michael S.; Bae, Hyun W.; Davis, Reginald J.; Gaede, Steven; Hoffman, Greg; Kim, Kee D.; Nunley, Pierce D.; Peterson, Daniel; Rashbaum, Ralph F.; Stokes, John; Ohnmeiss, Donna D.
Abstract : Study Design: This was a prospective, randomized, controlled multicenter trial. Objective: The purpose of this study was to compare clinical outcomes at 4-year follow-up of patients receiving cervical total disk replacement (TDR) with those receiving anterior cervical discectomy and fusion (ACDF). Summary of Background Data: ACDF has been the traditional treatment for symptomatic disk degeneration. Several studies found single-level TDR to be as safe and effective as ACDF at ≥2 years follow-up. Methods: Patients from 23 centers were randomized in a 2:1 ratio with 164 receiving the investigational device (Mobi-C Cervical Disc Prosthesis) and 81 receiving ACDF using an anterior plate and allograft. Patients were evaluated preoperatively and 6 weeks, 3, 6, 12, 18, 24, 36, and 48 months postoperatively. Outcome assessments included a composite success score, Neck Disability Index, visual analog scales assessing neck and arm pain, patient satisfaction, major complications, subsequent surgery, segmental range of motion, and adjacent-segment degeneration. Results: The composite success rate was similar in the 2 groups at 48-month follow-up. Mean Neck Disability Index, visual analog scale, and SF-12 scores were significantly improved in early follow-up in both groups with improvements maintained throughout 48 months. On some measures, TDR had significantly greater improvement during early follow-up. At no follow-up were TDR scores significantly worse than ACDF scores. Subsequent surgery rate was significantly higher for ACDF compared with TDR (9.9% vs. 3.0%, P <0.05). Range of motion was maintained with TDR having a mean baseline value of 8 degrees compared with 10 degrees at 48 months. The incidence of adjacent-segment degeneration was significantly higher with ACDF at inferior and superior segments compared with TDR (inferior: 50% vs. 30%, P <0.025; superior: 53% vs. 34%, P <0.025). Conclusions: Significant improvements were observed in pain and function. TDR patients maintained motion and had significantly lower rates of reoperation and adjacent-segment degeneration compared with ACDF. This study supports the safety and efficacy of TDR in appropriately selected patients.